Location and Single-Phase Fault Data Monitoring System Using ESP8266 via Blynk and Telegram - Duhi, Sahrul; Tansa, Salmawaty; Dako, Rahmat Deddy R.; Wahab Musa, Wahab Musa; Abdussamad, Syahrir; Tolago, Ade Irawaty (Jambura Journal of Electrical and Electronics Engineering, 2025)
The increasing consumption of electrical energy highlights the need for an efficient power monitoring system. This research develops an Internet of Things (IoT)-based single-phase fault monitoring system capable of detecting power outages and overcurrents, and providing real-time location notifications. The system is designed using a PZEM-004T power sensor for data acquisition, an ESP8266 microcontroller as a processing unit, a Blynk platform for visualization, and a Telegram-integrated NEO6M GPS module for automatic notification. Test results show that the system successfully detects and accurately informs power outages (current 0 A) and overcurrents (exceeding 1 A), sending notifications complete with a Google Maps link to the fault location. This system provides an effective and responsive solution for power outage management, contributing to improved operational and maintenance efficiency link via Telegram. The device testing was successfully conducted using the NEO 6M GPS module to determine the fault location.Peningkatan konsumsi energi listrik menyoroti kebutuhan akan sistem monitoring daya yang efisien. Penelitian ini mengembangkan sebuah sistem pemantauan gangguan satu fasa berbasis Internet of Things (IoT) yang mampu mendeteksi kondisi listrik padam dan arus lebih, serta memberikan notifikasi lokasi real-time. Sistem dirancang menggunakan sensor daya PZEM-004T untuk akuisisi data, mikrokontroler ESP8266 sebagai unit pemroses, platform Blynk untuk visualisasi, dan modul GPS NEO6M terintegrasi Telegram untuk notifikasi otomatis. Hasil pengujian menunjukkan bahwa sistem berhasil mendeteksi dan secara akurat menginformasikan kondisi listrik padam (arus 0 A) dan arus lebih (melebihi 1 A), mengirimkan notifikasi lengkap dengan link Google Maps lokasi gangguan. Sistem ini menyediakan solusi yang efektif dan responsif untuk manajemen gangguan listrik, berkontribusi pada peningkatan efisiensi operasional dan pemeliharaan